Different effects of the Cdx1 and Cdx2 homeobox genes in a murine model of intestinal inflammation. Issue 12 (26th June 2007) - Calon, A; Gross, I; Lhermitte, B; Martin, E; Beck, F; Duclos, B; Kedinger, M; Duluc, I; Domon-Dell, C; Freund, J-N
Abstract : Aims: The CDX1 and CDX2 homeoproteins are intestine-specific transcription factors regulating homeostasis. We investigated their relevance in experimentally-induced intestinal inflammation. Methods: The response to intestinal inflammation induced by dextran sodium sulfate (DSS) was compared in wild type, Cdx1 -/- and Cdx2 +/− mice. Intestinal permeability was determined in wild type and Cdx2 +/− mice. Protein-protein interactions were investigated by co-immunoprecipitation and GST-pulldown, and their functional consequences were assessed using Luciferase reporter systems. Results: Heterozygous Cdx2 +/− mice, but not Cdx1 -/- mice, were hypersensitive to DSS-induced acute inflammation as all these mice showed blood in the stools at day 1 of DSS treatment. Hypersensitivity was associated to a 50% higher intestinal permeability. In Cdx2 +/- mice, the colonic epithelium was repaired during the week after the end of DSS treatment, whereas two weeks were required for wild type animals. Subsequently, no colonic tumour was observed in Cdx2 +/− mice subjected to 5 repeated cycles of DSS, in contrast to the 2.7 tumours found per wild type mouse. Based on the fact that Smad3 +/− mice, like Cdx2 +/− mice, better repair the damaged intestinal epithelium, we found that the CDX2 protein interacts with SMAD3, independently of SMAD4, resulting in a 5-fold stimulation of SMAD3 transcriptional activity. CDX1 also interacted with SMAD3 but it inhibited by 10-fold the SMAD3/SMAD4-dependent transcription. Conclusion: The Cdx1 and Cdx2 homeobox genes have distinct effects on the outcome of a pro-inflammatory challenge. This is mirrored by different functional interactions of the CDX1 and CDX2 proteins with SMAD3, a major element of the TGFβ signalling pathway.